Recognition of Emotions From Facial Point-Light Displays - Bidet-Ildei, Christel; Decatoire, Arnaud; Gil, Sandrine (Frontiers in Psychology, 2020)
Facial emotion recognition occupies a prominent place in emotion psychology. How perceivers recognise messages conveyed by faces can be studied in either an explicit or an implicit way, and using different kinds of facial stimuli. In the present study, we explored for the first time how facial point-light displays (i.e., biological motion with minimal perceptual properties) can elicit both explicit and implicit mechanisms of facial emotion recognition. Participants completed tasks of explicit or implicit facial emotion recognition from point-light displays. Results showed that point-light stimuli are sufficient to allow facial emotion recognition, be it explicit and implicit. We argue that this finding could encourage the use of point-light displays in research on the perception of emotional cues from faces.